High Depth‐of‐Discharge Zinc Rechargeability Enabled by a Self‐Assembled Polymeric Coating. Issue 38 (27th August 2021) - Arnot, David J.; Lim, Matthew B.; Bell, Nelson S.; Schorr, Noah B.; Hill, Ryan C.; Meyer, Andrew; Cheng, Yang‐Tse; Lambert, Timothy N.
Abstract: Zinc has the potential for widespread use as an environmentally friendly and cost‐effective anode material pending the resolution of rechargeability issues caused by active material loss and shape change. Here, a self‐assembled Nafion‐coated Celgard 3501 (NC‐Celgard) separator is shown to enable unprecedented cycle life of a Zn anode in alkaline electrolyte at high depth‐of‐discharge (DODZn ). Using commercially relevant energy‐dense electrodes with high areal capacities of 60 mAh cm –2, Zn–Ni cells tested at 20% DODZn cells achieve over 200 cycles while 50% DODZn cells achieve over 100 cycles before failure. The 20% and 50% DOD cells deliver an average of 132 and 180 Wh L –1 per cycle over their lifetime respectively. Rechargeability is attributed to the highly selective diffusion properties of the 300 nm thick negatively charged Nafion coating on the separator which prevents shorting by dendrites and inhibits redistribution of the active material. Crossover experiments show that the NC‐Celgard separator is practically impermeable to zincate ([Zn(OH)4 ] 2– ), outperforming commercial Celgard, cellophane, Nafion 211 and 212 separators while still allowing hydroxide transport. This work demonstrates the efficacy of selective separators for increasing the cycle life of energy‐dense Zn electrodes without adding significant volume or complexity to the system. Abstract : A self‐assembled Nafion‐coated Celgard separator is shown to enable unprecedented cycle life of a Zn anode in alkaline electrolyte at high depth‐of‐discharge (DODZn ). Rechargeability is attributed to the highly selective diffusion properties of the 300 nm negatively charged Nafion coating on the separator which prevents shorting by dendrites and inhibits redistribution of the active material.